2015
DOI: 10.1371/journal.pone.0119949
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of the White Body of the Squid Euprymna tasmanica with Emphasis on Immune and Hematopoietic Gene Discovery

Abstract: In the mutualistic relationship between the squid Euprymna tasmanica and the bioluminescent bacterium Vibrio fischeri, several host factors, including immune-related proteins, are known to interact and respond specifically and exclusively to the presence of the symbiont. In squid and octopus, the white body is considered to be an immune organ mainly due to the fact that blood cells, or hemocytes, are known to be present in high numbers and in different developmental stages. Hence, the white body has been descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 104 publications
2
39
0
Order By: Relevance
“…The white body is a multi-lobed organ that wraps around the optic bundle [22, 31]. Haematopoietic development in the white body was first described in the common octopus O. vulgaris by Cowden (1972) [98], who identified primary, secondary and tertiary leukoblasts in histological sections.…”
Section: Cephalopod Haematopoiesis and Haemocyte Functionmentioning
confidence: 99%
See 4 more Smart Citations
“…The white body is a multi-lobed organ that wraps around the optic bundle [22, 31]. Haematopoietic development in the white body was first described in the common octopus O. vulgaris by Cowden (1972) [98], who identified primary, secondary and tertiary leukoblasts in histological sections.…”
Section: Cephalopod Haematopoiesis and Haemocyte Functionmentioning
confidence: 99%
“…The larger cells were more phagocytic and produced a more intense respiratory burst than the smaller cells [26]. However, a similar study found three haemocyte types in O. vulgaris , which were described as hyalinocytes, granulocytes, and haemoblast-like cells [22]. Such discrepancies demonstrate a need for a standardized characterization of the haemocyte populations in cephalopods.…”
Section: Cephalopod Haematopoiesis and Haemocyte Functionmentioning
confidence: 99%
See 3 more Smart Citations